Retinoic acid and fibroblast growth factor-2 play a key role on modulation of sex hormones and apoptosis in a mouse model of polycystic ovary syndrome induced by estradiol valerate - Ardeshir Moayeri; Ayoob Rostamzadeh; Amir Raoofi; Mohammad Jafar Rezaie; Zahra Abasian; Reza Ahmadi (Elsevier, 2020)
Objective: The main goal of the present study is to investigate the effects of retinoic acid and fibroblast growth factor-2 on serum levels of FSH and LH, histology, and apoptosis in the mouse model of Poly Cystic Ovary Syndrome (PCOS). Materials and methods: 80 female NMRI mice have been randomly divided into eight groups. Group 1 received normal saline as a control, and Group 2 received estradiol valerate (EV) at 4 mg/100 g of body weight. Moreover, Groups 3-4 were administered with RA (a dose of 0.05 μg/μl) and FGF2 (a dose of 0.01 μg/kg), respectively. Groups 5 and 6 respectively received the EV plus the RA (0.05 μg/μl) and FGF2 (0.01 μg/kg). Group 7 received the RA and FGF2 at doses corresponding to healthy mice, and Group 8 received the EV plus the RA + FGF2 (similar to previous doses). RA and FGF2 were injected three times per week for four weeks. Finally, histological and immunohistological parameters of the ovary were evaluated. Results: The study revealed that both single and combined injection of fibroblast growth factor-2 (FGF2) and retinoic acid (RA) in groups 5, 6, and 8 significantly reduced follicular diameters compared to group 2. Measurements confirmed that simultaneous injection of RA and FGF2 into polycystic mice significantly increased antral follicles, corpus luteum (CL), epithelial thickness, and oocyte diameter as well as decreased cystic follicles. Positive TUNEL cells that were considerably increased in the antral follicle of group 2 significantly decreased in the RA and FGF2 recipient groups, either alone or in combination. Besides, the injection of FGF2 increased preantral follicles and CL. Conclusion: The findings of the present investigation reveal that injection of RA and FGF2 has both protective and ameliorative effects that can promise new therapies for women with PCOS.